Advances in Genetic Manipulation of Obligate Intracellular Bacterial Pathogens - Beare, Paul; Sandoz, Kelsi; Omsland, Anders; Rockey, Daniel; Heinzen, Robert (Frontiers in Microbiology, 2011)
Infections by obligate intracellular bacterial pathogens result in significant morbidity and mortality worldwide. These bacteria include Chlamydia spp., which causes millions of cases of sexually transmitted disease and blinding trachoma annually, and members of the α-proteobacterial genera Anaplasma, Ehrlichia, Orientia and Rickettsia, agents of serious human illnesses including epidemic typhus. Coxiella burnetii, the agent of human Q fever, has also been considered a prototypical obligate intracellular bacterium, but recent host cell-free (axenic) growth has rescued it from obligatism. The historic genetic intractability of obligate intracellular bacteria has severely limited molecular dissection of their unique lifestyles and virulence factors involved in pathogenesis. Host cell restricted growth is a significant barrier to genetic transformation that can make simple procedures for free-living bacteria, such as cloning, exceedingly difficult. Low transformation efficiency requiring long term culture in host cells to expand small transformant populations is another obstacle. Despite numerous technical limitations, the last decade has witnessed significant gains in genetic manipulation of obligate intracellular bacteria including allelic exchange. Continued development of genetic tools should soon enable routine mutation and complementation strategies for virulence factor discovery and stimulate renewed interest in these refractory pathogens. In this review, we discuss the technical challenges associated with genetic transformation of obligate intracellular bacteria and highlight advances made with individual genera.